2020
DOI: 10.1021/acs.chemmater.0c03740
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Chemistry That Leads to High Valley Degeneracy in PbTe

Abstract: PbTe is one of the highest-performing known thermoelectric materials. Much of its promising thermoelectric performance can be attributed to high valley degeneracy due to having a valence band minimum (VBM) and conduction band maximum (CBM) at the L-point in the first Brillouin zone, which has 4-fold degeneracy, instead of at Γ, which has 1-fold degeneracy. The existence of the VBM at L has been explained by the contribution of Pb-s states that make up the valence band edge. However, the dominance of Te-p state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 43 publications
(116 reference statements)
3
37
0
Order By: Relevance
“…In recent years, with continuous exploration of interatomic interactions, a few other rational explanation have emerged to account for the fundamental nature of a part of materials containing ns 2 cations. [ 304 ] In particular, Wuttig's group have raised a bonding mechanism dubbed as “metavalent” bonding (MVB) as an alternative approach. [ 305 ] From their point of view, the degrees of electron sharing (ES) and electron transfer (ET) between adjacent atoms are key factors affecting the chemical bonding mechanisms.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with continuous exploration of interatomic interactions, a few other rational explanation have emerged to account for the fundamental nature of a part of materials containing ns 2 cations. [ 304 ] In particular, Wuttig's group have raised a bonding mechanism dubbed as “metavalent” bonding (MVB) as an alternative approach. [ 305 ] From their point of view, the degrees of electron sharing (ES) and electron transfer (ET) between adjacent atoms are key factors affecting the chemical bonding mechanisms.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Thus, by mapping a series of materials, including PbX (X = S, Se, Te), Sb 2 Te 3 , Bi 2 X 3 (X = Se, Te), and inorganic halide perovskites, into a 2D space with the ES and ET as two coordinates, they found MVB had well‐defined borders to covalent, and iono‐covalent regions, indicating its distinction. [ 229–307 ] Such a map demonstrated that the MVB mechanism approximately possessed one shared electron and moderate electron transfer between adjacent atoms. This predictive model can also give rise to the favorable characteristics in above materials, including large Born effective charge, high optical dielectric constants, strong optical interband transition, etc.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…This had PbTe classified as a 'metavalent' compound according to a recent classification. [19] However, it is also commonly stated that the physico-chemical behavior of PbTe is linked to lone pairs, [30] although p-orbital overlap was shown recently to be responsible for the valence band dispersion [59] therefore questioning the relevance of lone pairs. Figure 9 shows a valence charge density (only s and p electrons) that is very much localized onto the atoms' cores, in agreement with the charge transfer of 0.7 electrons.…”
Section: Pbte: a Cubic Thermoelectric Compoundmentioning
confidence: 99%
“…This had PbTe classified as a "metavalent" compound according to a recent classification. [19] However, it is also commonly stated that the physicochemical behavior of PbTe is linked to lone pairs, [30] although p-orbital overlap was shown recently to be responsible for the valence band dispersion, [59] therefore questioning the relevance of lone pairs.…”
Section: Pbte: a Cubic Thermoelectric Compoundmentioning
confidence: 99%
See 1 more Smart Citation